2021
DOI: 10.1136/bmjopen-2020-046928
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: indigenous human papillomavirus and oropharyngeal squamous cell carcinoma study - a prospective longitudinal cohort

Abstract: PurposeOur aims are to: (1) estimate prevalence, incidence, clearance and persistence of oral human papillomavirus (HPV) infection among Indigenous Australians; (2) identify risk factors associated with oropharyngeal squamous cell carcinoma (OPSCC)-related HPV types (HPV 16 or 18); (3) develop HPV-related health state valuations and; (4) determine the impact on OPSCC and cervical cancers, and the cost-effectiveness of extending publicly-funded HPV vaccination among Indigenous Australians.ParticipantsParticipan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…25 Unfortunately this study did not distinguish between vaccinated and unvaccinated individuals when describing HPV-positivity, thus it is unclear whether lack of vaccination led to this percentage increase. 25 Katz et al in 2020, used a cross-sectional study format and interrogated the correlation of OPC with HPVvaccination using hospital databases (Table 5) 26 . They found a relative risk ratio increase of 23.8 (P = 0.0015) of developing oropharyngeal cancer in the male subgroup if they were not vaccinated 26 .…”
Section: Study Characteristicsmentioning
confidence: 87%
See 2 more Smart Citations
“…25 Unfortunately this study did not distinguish between vaccinated and unvaccinated individuals when describing HPV-positivity, thus it is unclear whether lack of vaccination led to this percentage increase. 25 Katz et al in 2020, used a cross-sectional study format and interrogated the correlation of OPC with HPVvaccination using hospital databases (Table 5) 26 . They found a relative risk ratio increase of 23.8 (P = 0.0015) of developing oropharyngeal cancer in the male subgroup if they were not vaccinated 26 .…”
Section: Study Characteristicsmentioning
confidence: 87%
“…An ongoing prospective longitudinal cohort study into Indigenous Australians by Jamieson et al, demonstrated evidence of HPV-vaccination in only 8.3% of participants, but did not distinguish between males and females (Table 5). 25 The researchers followed 910 individuals over 12 months obtaining data on HPV-positivity, HPV-vaccination as well as various other healthcare related data. They noted that 3.3% of males were positive for oral HPV16/18 and this increased to 3.9% at 12 months follow up.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One interesting finding of our study is the high prevalence (37.5%) of HPV infection in the normal oral mucosa of healthy individuals. Other studies of cancer-free individuals reported values from 0% to 81.1% in normal oral mucosal cells, exfoliated cells from normal tonsils, or oral gargles and tonsillar washings [ 37 , 38 , 45 , 46 , 86 , 90 , 91 , 92 , 93 ]. In Polish population, a low frequency (1.08%) was observed in normal oral squamous cells [ 38 ], while a higher prevalence in oropharyngeal swabs was observed in couples (19.8% in women and 28.4% in men) and in 5.6% of couples, both partners were infected (in 81.8% of cases with identical HPV types).…”
Section: Discussionmentioning
confidence: 99%
“…Even so, it is currently unknown what effect FEH lesions coinfected with high-risk genotypes, such as HPV16 or HPV18, have on a possible malignant transformation, and the correlation to other HPV-positive oral indications, since they have not been systematically reported. This type of study is currently ongoing among indigenous Australians [ 25 ].…”
Section: Human Papillomavirus Genotypes In Focal Epithelial Hyperplasiamentioning
confidence: 99%